Takaran Biochar dan Level Teh Kompos Terhadap Pertumbuhan dan Hasil Tanaman Kacang Tanah (Arachis hypogaea L.) di Lahan Kering Entisol - Asep Ikhsan Gumelar; Marselina Seo (Fakultas Pertanian, Universitas Timor, 2021)
Research aimed at knowing the influence of biochar and compost tea level with different levels to increase the growth and yield of peanut plants in Entisol dry land. This research was conducted on 13 July 2019 in experimental Land of the Faculty of Agriculture University of Timor, village of Sasi, Kefamenanu-Timor Tengah Utara, East Nusa Tenggara. Research using the 3 x 3 factorial randomized block design (RBD) with three repeated. The first factor is doses Biochar which is based on 3 (three) levels: without Biochar 0 t/ha, Biochar 5 t/ha, Biochar 10 t/ha. The second factor is the Compost tea Level which is based on 3 (three) levels: no compost tea, 50 mL of Compost tea, 150 mL of Compost tea. Each was repeated 3 times so that there were 27 units of experiments. Interaction of Administration without biochar and compost tea level 150 ml/plant affects the ground temperature 21 HST While the combination treatment of biochar 10 t/ha and compost tea level 150 ml/plant interact positively (P < 0.005) in influencing the number of cropping pods and weight of one hundred seeds. Combination of 10 t/ha biochar and compost tea level 150 ml/plant is the best treatment and average does not give noticeable effect on each treatment level.